2006
DOI: 10.1103/physreva.74.033801
|View full text |Cite
|
Sign up to set email alerts
|

Slow light with large fractional delays by spectral hole-burning in rubidium vapor

Abstract: We report on the experimental realization of large fractional pulse delays in a hot, Doppler-broadened rubidium vapor. A pump laser burns a deep spectral hole in the inhomogeneously broadened vapor. The delay is shown to be widely tunable by both power broadening the resonance and frequency modulating the pump laser. The simplicity of the scheme opens up the possibility for practical optical delays and buffers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 16 publications
0
26
0
2
Order By: Relevance
“…Numerical solutions are obtained by solving the above pulse-propagation equations from (2) to (6). The results are shown in the following contents.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical solutions are obtained by solving the above pulse-propagation equations from (2) to (6). The results are shown in the following contents.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…It has several advantages including the simplicity, the high pump efficiency, the compatibility with existing telecommunication systems, and room-temperature operation [3], compared with other slow light techniques such as coherent population oscillations [4], electromagnetically induced transparency [5], and saturated absorption [6]. So it has shown that SBS delay line is a promising technique for optical buffers and all-optical switches.…”
Section: Introductionmentioning
confidence: 98%
“…Rapid tuning of the delays has also been demonstrated by varying the modulation frequency in a two-laser, pump-probe configuration. 9 Precise absorption models which fully account for the hyperfine structure can be computationally expensive. Therefore it is often advantageous to approximate the absorption coefficient or complex index of refraction as the summation of Lorentzian lineshapes at a pair of resonant frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In ref [83], delays of 2 bit intervals were achieved for a moderate bandwidth of 100 MHz but only in a 40 cm long Rb vapor delay line. Since the background absorption in the hole burning is always high, it is the dispersion of loss that causes the signal distortion and is in fact an ultimate limitation in this scheme.…”
Section: Figure 17 Refractive Index Profile For Slow Light In Eit 20mentioning
confidence: 99%
“…By changing the spectrum of the coupling, for instance, using intensity or frequency modulation, one can change   [83] to achieve the maximum delay without distortion for a given bit rate. In ref [83], delays of 2 bit intervals were achieved for a moderate bandwidth of 100 MHz but only in a 40 cm long Rb vapor delay line.…”
Section: Figure 17 Refractive Index Profile For Slow Light In Eit 20mentioning
confidence: 99%